Beyond the bases : the status of territorial sovereignty in the Australian Antarctic Territory - Indiah Hodgson-Johnston (2018)
This thesis critically examines two aspects of international law related to Australia's territorial sovereignty over the Australian Antarctic Territory (the AAT): the effectiveness of Australia's authority in the AAT, and the present territorial status of the AAT under the Treaty. It does this through a conceptual analysis of both the union and the divorce of the two central elements of territorial sovereignty: imperium and dominium. Part I provides an overview of the theories and principles of statehood, territorial sovereignty and title to territorial sovereignty as applied to remote and unpopulated dependencies. Part II addresses the dominant argument within the literature by examining the notion of effectiveness and extent of Australia's title to territorial sovereignty over the AAT. It constructs this analysis through the lens of the union of imperium and dominium over the AAT, and by utilising contemporary hierarchies of evidence that have emerged in international law in the post-war shift from territorial expansionism. Part III of this work addresses a gap in the literature by discussing the mechanisms of art IV of the Antarctic Treaty and how this disaggregates the imperium from the dominium. This aim is achieved by comparing the territorial aspects of the Treaty with other territorial regimes, such as Guantanamo Bay, the Mandated Territories, and United Nations Administrative regimes. The aim of this comparison is to provide a framework of analysis and discourse for the present, and perhaps perpetually enduring, status of the AAT, to step away from the vague descriptors such as 'frozen' and 'suspended'. This thesis shows that, while in a relative sense the title to territorial sovereignty in Antarctica is strong, that its legislative framework lacks specificity and clarity. It is also observed that the AAT's administrative framework is heavily concentrated in a highly specialised structure which is deeply ensconced in operations, in contrast to the separate governance structures typical of the other ...